1997
DOI: 10.1007/bf02388140
|View full text |Cite
|
Sign up to set email alerts
|

High submucosal blood flow and low anastomotic tension prevent anastomotic leakage in rabbits

Abstract: In many cases of long-gap congenital esophageal atresia, direct anastomosis is difficult. In these cases, the esophagus is first lengthened by myotomy before anastomosis. We determined the degree of submucosal blood flow and/or approximation force at the site of anastomosis in rabbits after (1) separation of the esophagus from the outer membrane, (2) 1 cm and 2 cm resection of the esophagus, and (3) circular or spiral myotomy of the esophagus after 2 cm resection. In the first experimental group, submucosal bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…[15] showing higher rates of colon anastomotic leakage in patients with decreased tissue oxygen tension. Subsequently, animal models have confirmed the importance of adequate blood flow and oxygenation for the creation of a sustainable anastomosis [11, 13]. Anegg et al [16] demonstrated that decreased oxygen tension at the esophago-enteric anastomosis is associated with an increased leak rate in humans.…”
Section: Introductionmentioning
confidence: 99%
“…[15] showing higher rates of colon anastomotic leakage in patients with decreased tissue oxygen tension. Subsequently, animal models have confirmed the importance of adequate blood flow and oxygenation for the creation of a sustainable anastomosis [11, 13]. Anegg et al [16] demonstrated that decreased oxygen tension at the esophago-enteric anastomosis is associated with an increased leak rate in humans.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the LDF signals can be obtained from the mucosa and submucosa due to the loss of mucosa, marked expansion of the submucosa, and presence of dilated blood vessels within this layer in GERD 23,24 . Previous studies showed the peak blood flow to be in the esophageal submucosa; the submucosal blood flow was 1.5 times greater than that of the mucosa 26,27 . Considered together, we believe that while the measured blood flow in our study represents that of the mucosa and submucosa, it reflects mainly that of the latter layer.…”
Section: Discussionmentioning
confidence: 43%
“…23,24 Previous studies showed the peak blood flow to be in the esophageal submucosa; the submucosal blood flow was 1.5 times greater than that of the mucosa. 26,27 Considered together, we believe that while the measured blood flow in our study represents that of the mucosa and submucosa, it reflects mainly that of the latter layer. The correlations between the thickness of the whole esophageal wall and that of the mucosal and submucosal layers with esophageal mucosal/submucosal blood flow identified in the present study suggest that the increased blood flow does not only represent a response to humoral and neural factors, but also reflects expansion of the mucosal and submucosal layer caused by inflammatory processes and regenerative changes.…”
Section: Discussionmentioning
confidence: 61%
“…Fujiwara et al [14] demonstrated that approximation force and submucosal blood flow at the site of an anastomosis are important factors for preventing anastomotic leakage in an experimental rabbit model. Moreover, circular myotomy was superior to spiral myotomy for reduction of the approximation force at the site of the anastomosis.…”
Section: Discussionmentioning
confidence: 98%